Role of the family support division (Bahagian Sokongan Keluarga) of the Syariah judiciary department Malaysia in helping single mothers in Malaysia - Awang, Abd. Rahman (s.n, 2013)
In Malaysia, it is reported that in the year 2000 there were 128,810 single parent families, and the number has been increasing. Past research had found that single parent families and their children experienced more difficulties in the context of family life and well-being than two-parent families (Anjli Panala K. Doshi, 2005. From the legal perspective, one of the problems of single parents is the difficulty of enforcement of the alimony order granted by the courts upon divorce. This division is to handle related to the enforcement of the maintenance orders issues